Artisanal fisheries production in the coastal zone of Itaipu, Niterói , RJ, Brazil (Brazilian Journal of Oceanography, 2007)
Artisanal fisheries in the coastal zone of Itaipu-RJ play an important role in the local market, but little is known about production and productivity of the fisheries. From April 2001 to March 2003, we monitored a total of 618 landings from the beach-seine (99), the gill nets ("corvineira" - 331, "linguadeira" - 40 and "rede alta" - 25), the hook and line (98), the squid jigging (17), and the spear fishing and trap fisheries (five and three, respectively). The total monitored production was 21866 kg and the catch per unit effort (CPUE) 35.4 kg.trip-1. Considering the number of effective fishing days and the average daily production per fishing gear, the annual production was estimated at 136687 kg (0.2% of the state's production in 2004). Predominant resources were: Micropogonias furnieri,Trichiurus lepturus, squids (Loligo spp.), clupeiform fishes (Sardinella brasiliensis, Cetengraulis edentulus, Pellona harrowerii and Harengula clupeola), Eucinostomus spp., Cynoscion spp., Menticirrhus spp., Caranx crysos and Selene setapinnis. The combined analysis using hierarchical and non-hierarchical classification methods, separated four fishing gears and five species groups, based on their similarity patterns, identifying gears that most effectively capture the different fish groups. The beach-seine was less selective and most productive fishery in the summer. The "corvineira" was the second most productive fishery with higher yields in the summer and fall. Catches of "linguadeira" included rays and Paralychthys spp., wherereas the "rede alta" caught primarily M. furnieri,Mugil spp. and sharks.